Visions for Urban Landscape Sustainability, Past, Present and Future - Salem, Dina (European Journal of Sustainable Development, 2016)
Sustainable landscape is widely understood as a key contributor to urban sustainability for the fact that all landscapes has a social, economic, cultural and ecological function for the community‘s well-being and quality of life. This paper briefly reviews the concepts of landscape planning and its role in creating urban quality even before sustainability oriented developments; Sustainable development and the changes in its interpretation as well as visions for landscape sustainability are demonstrated, defined and classified. Challenges facing sustainable landscape planning are discussed. Finally, the paper discusses how our future urban open spaces could be sustainable and how does this contribute to urban sustainability pillars. Keywords: Sustainable urban landscape, socio-ecological sustainability, green infrastructure